2022
DOI: 10.2166/wcc.2022.385
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of soft computing techniques for forecasting daily reference evapotranspiration

Abstract: Precise information on evapotranspiration aids in efficient irrigation scheduling and optimal crop production. In this study, soft computing tools, namely, artificial neural network (ANN) and k-nearest-neighbor (KNN) models, were evaluated by comparing with the Penman–Monteith (PM) model using climatic data from 1990 to 2020 of the Indian Agricultural Research Institute (IARI) farm, New Delhi, India. Results revealed that the ANN model with sigmoid activation function and the L-BFGS learning algorithm was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…For example, Rajput et al. (2023) evaluated ANN and KNN algorithms and compared them with the standard PM method using climatic data for New Delhi, India. The study found that the ANN model outperformed the KNN model in forecasting ET 0 when all input variables were considered.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Rajput et al. (2023) evaluated ANN and KNN algorithms and compared them with the standard PM method using climatic data for New Delhi, India. The study found that the ANN model outperformed the KNN model in forecasting ET 0 when all input variables were considered.…”
Section: Discussionmentioning
confidence: 99%
“…Indian agriculture sector consumes approximately 90% of the total freshwater resources available in the country due to improved groundwater withdrawal infrastructures and poor on‐farm irrigation efficiency (Jain et al., 2019). Thus, irrigated agriculture has an important role in meeting the food need of the ever‐increasing population (Rajput et al., 2022). However, due to the rising demand for freshwater availability among different water use sectors, the freshwater availability for agriculture is projected to be reduced significantly (Kumari et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations